Evaluating Teachers' Perspectives on Integrating Life Skills into the Basic Science Curriculum to Enhance Students’ Upskilling - Okeke, Tobechukwu Ebele (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This study investigates junior secondary school teachers' perspectives on integrating life skills into the basic science curriculum to enhance students’ upskilling in Anambra State. Employing a survey design, self-structured questionnaires were distributed via Google survey to 80 participating teachers. The research instrument's content validity was ensured through professional input, and reliability was confirmed with a Cronbach's coefficient alpha of 0.77. Demographic data were analyzed using frequency counts and percentages, while mean, standard deviation, and t-tests were employed to assess research questions and hypotheses. The findings provide a comprehensive understanding of teachers' viewpoints on life skills integration, emphasizing challenges and opportunities in the context of basic science education. This study contributes to educational discourse, offering insights that can inform curriculum design and support systems to enhance student upskilling through effective life skills integration.